O turismo rural como alternativa de desenvolvimento econômico para o município de Bofete-SP - Martins, Danilo Machado Rodrigues (Universidade Federal de São Carlos, 2024)
Once with an economy based on agriculture and cattle farming, since the middle of 20th century, the city of Bofete has been diversifying it. Over the decades, sector such as commerce and services have been gaining more space in the city´s economic composition. Tourism, in addition to bringing employment and income opportunities, has been playing a key role in terms os alternatives for sustainable economic development. With extremely important attractions and support services for the activity, the city has great potential for exploring tourism. Based on this, the present work seeks not only to identify potentialities and the relationship between supply and demand in the city, but also the actions implemented by the local authorities, in addition to documenting socioeconomic and environmental aspects, preserving its identity, and highlighting tourist activity, especially rural tourism, as part of its economic development.
The rural tourism as an alternative for economic development in the municipality of Bofete-SP
Keywords: Turismo Rural; Políticas Públicas; Desenvolvimento Econômico; Rural Tourism; Public Policy; Economic Development; CIENCIAS SOCIAIS APLICADAS::TURISMO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA